2016
DOI: 10.3390/ijerph13111092
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Discontinuity of Age Relations in Cognitive Functioning, General Health Status, Activity Participation, and Life Satisfaction between Young-Old and Old-Old Age

Abstract: Health research suggests that findings on young-old adults cannot be generalized to old-old adults and thus that old-old age seems not a simple continuation of young-old age due to qualitative changes that result in a discontinuity in old age. Specifically, it would be of conceptual and methodological importance to inform research regarding estimates around which chronological age the beginning of old-old age could be placed at a population level, and whether this is universal or domain-specific. To derive suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…As for walking, the situation is quite different. In healthy individuals gait is a rather symmetric function (Viteckova et al, 2018), controlled by basic spinal motor programs that keep movement synchronization (Ivanenko, Poppele, & Lacquaniti, 2006). However, under specific contexts like in dual-tasking, the nervous system needs to integrate additional sensorimotor information by utilizing higher-level cortical functions and volitional actions.…”
Section: Why Does Lateralized Focus Of Auditory Attention Influence Gmentioning
confidence: 99%
See 2 more Smart Citations
“…As for walking, the situation is quite different. In healthy individuals gait is a rather symmetric function (Viteckova et al, 2018), controlled by basic spinal motor programs that keep movement synchronization (Ivanenko, Poppele, & Lacquaniti, 2006). However, under specific contexts like in dual-tasking, the nervous system needs to integrate additional sensorimotor information by utilizing higher-level cortical functions and volitional actions.…”
Section: Why Does Lateralized Focus Of Auditory Attention Influence Gmentioning
confidence: 99%
“…These events perturb central generator patterns for locomotion (Ivanenko et al, 2006;Robinson & Kiely, 2017). In aging, walking becomes a more demanding action and more involvement of executive functions and attention is required (Yogev-Seligmann, Hausdorff, & Giladi, 2008).…”
Section: Why Does Lateralized Focus Of Auditory Attention Influence Gmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, the results demonstrated that the NRCMS enrolees had the highest rate of outpatient satisfaction because the plan provided higher reimbursement levels and substantially invested in village and township levels as well as primary medical institutions to access primary‐level care, demonstrating rational distribution and fully used medical resources . The rural residents' unsophisticated character, their trust in family doctors and first contact care of the community, along with step by step referral gradient, help explain the higher satisfaction rate of NRCMS enrolees.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 89%
“…Therefore, effective measures, such as shifting qualified human resources and technologies to primary medical institutions, and enhanced quality that take advantage of the family doctor system to regulate and reinstitute sequential medical order (referral from primary medical institutions to higher level medical institutions) as well as strengthen the service delivery system could have short‐term satisfaction implications, which will lead to both satisfaction and rational medical order in the long run …”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%